ANALISIS BREAK EVENT POINT (BEP) PADA USAHA BATAKO BAHAR - Ahmad Tomu (JURNAL ULET (Utility, Earning and Tax), 2018)
The aim of this research are: 1) To know the salling (unit and rupiah) must be done by Batako Bahar business to be at a point BEP. 2) To know the salling (unit and rupiah) must be done by Batako Bahar business to achieve profit is planned amount to Rp 540.000.000, - 3) To know the percentage of sold decrease (based on budget) to be at a point BEP. The data collection instrument used in this research are: 1) Documentation, which collecting note obtained from a varies written sources, whether they are from Batako Bahar and also from other business which has relationship with the reserach, documentation is a note which taken in the past such as notes, books and others. 2) Interviews, is a method of collecting the data by question and answer, or communicate directly with people who has related with the problems in the research to get the better data). The results of research show that 1) The minimal sales volume that should be done by Batako Bahar to be at a point BEP amounted to 252.370 units, or Rp 656.162.532; 2) The volume of sales that must be done by Batako Bahar achieve the planned profit during 2015 amount to Rp 540.000.000,- is 966 362 units or Rp 2.512.542.955; 3) the percentage decrease in salling (on a budget) to be at a point BEP is 68%.